Exploring bleeding in oral anticoagulant users: assessing incidence by indications and risk factors in the entire nationwide cohort - Jeong, Jonghyun; Heo, Kyu-Nam; Lee, Suhyun; Ah, Young-Mi; Min, Sangil; Han, Ji Min; Lee, Ju-Yeun (Frontiers in Pharmacology, 2024)
Background Oral anticoagulants (OACs) are essential for the prevention and treatment of thromboembolic disorders, but bleeding, a major complication, can have a fatal impact on the patient’s treatment. Objectives We aimed to estimate the nationwide, real-world incidence rate of bleeding in patients taking OACs and confirm the incidence by indications and risk factors. Methods This cross-sectional study identified OAC users from April 1 to December 31, in both 2019 and 2020, using the HIRA-NPS database. The primary outcome variables were the incidence rate of major bleeding events during OAC treatment and within 30 days of treatment discontinuation. We estimated the adjusted incidence rate ratio (aIRR) in subpopulations. Results Among 18,822 OAC users, the incidence rate of major bleeding was 27.9 (95% CI: 24.6–31.5) per 1,000 person-years. The incidence rate of major bleeding was higher in patients with a bleeding history, with an aIRR of 11.51; those at high bleeding risk (HAS-BLED score ≥3), with an aIRR of 1.51; those with high CCI scores ≥3, with an aIRR of 1.88; and those with liver disease, with an aIRR of 1.41. For indications, compared to patients with nonvalvular atrial fibrillation (NVAF), the aIRR of major bleeding was significantly higher at an aIRR of 2.35 in patients undergoing VTE treatment. Patients with ischemic stroke showed a higher incidence of major bleeding with an aIRR of 2.13 than NVAF patients. The aIRR of major bleeding in the oral anticoagulant group, compared to the matched control group, was 2.25 (95% CI: 1.93–2.63). Conclusion These findings may be useful for implementing strategies to improve the evaluation and management of anticoagulation-related bleeding.